Ato ni Bai exploring the future of durian fruit agritourism through a postharvest research complex - Nierre, Jieson N.; Ruby Teresa M. de Leon (Quezon City College of Architecture, University of the Philippines Diliman, 2025)
A project contributing to the favorable progress of the Philippine durian industry and
its current industrial success brought about issues regarding the unpreparedness of
Filipino producers in regard to production volume and quality, exposing multifaceted
faults from comparatively primitive farming techniques to barely functioning
postharvest facilities. A constructivist approach in examining the different experiences
and problems of stakeholders in the industry was utilized, strengthened by qualitative
data gathering through direct interviews and precedent visits. The design proposal
aims to develop a fully functional postharvest research center, highlighting the
importance of knowledge exchange as an integral part of research, equipped with an
extension and institution cooperation facility containing a production warehouse
reserved for the facility's own processing or for the use of small-scale farmers,
traders, exporters, and processors, ameliorating the smaller integral stakeholders of
the industry while serving as a symbol for the Philippines' durian agritourism
through a production-oriented approach delivering the services that are typically
done in between the farm-to-table experience. Backed up by intensive architectural
translations, the intricacies of a postharvest research complex were explored to
uncover the inherent properties of agritourism.
Include appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Postharvest; Agritourism